Mejoramiento del plan de manejo de residuos sólidos de la localidad de Cartavio, en el distrito de Santiago de Cao - García Diestra, Ricardo (2018)
The research develops the improvement of the Solid Waste Management Plan (PMRS) of the town of Cartavio for the current Environmental Management of the district of Santiago de Cao, optimizing the public cleaning service, strengthening the stages of generation, collection, treatment and transportation of solid waste through the implementation of collection routes for the units assigned to the street collection and sweeping service, and the establishment of strategic points for the collection of solid waste that reduced the collection time and operating costs to the time they increased the scope of the service; Likewise, the reactivation of the Program of "Segregation at the source and selective collection of household solid waste" was carried out with the objective of reducing the environmental problems with greater incidence in the locality, as well as the current regulations. Methodologies were used such as the one proposed by the Ministry of the Environment for the development of the Solid Waste Management Plan and having as main reference the Study of generation and characterization of solid waste of the District of Santiago de Cao prepared in September 2016, supplemented with programs of training and environmental education directed to the personnel and educational institutions. The improvement of the PMRS through the evaluation of results concludes that the increase in the scope of the collection service is total for all the zones of the locality daily, reducing operational costs in S / .2948 projected annually and referred to the saving in consumption of fuel and the establishment of a Program of Segregation in the Source that recovered around 2.9 Ton / month of reusable inorganic solid waste